D&R OBLIGATIONS OF OIL PRODUCING COMPANIES: ECONOMIC AND LEGAL MECHANISMS FOR IMPLEMENTATION - M. A. Valishvili (Publishing House of the State University of Management, 2020)
One of the most “dirty” sectors of the economy is traditionally considered mining and processing industries, while they are less equipped with advanced technologies for cleaning production and consumption waste. The implementation of obligations by oil producing companies to restore the environment is one of the most important areas of state policy. At the same time, the state uses all possible economic and legal instruments to influence subsoil users: from forcing them to set strict environmental standards and levy fines for non-compliance, to encouraging companies themselves to develop along the “green” path, offering various benefits and preferences in return. An overview of the main directions of implementation of D&R obligations of the largest oil and gas companies, as well as the relationship of these obligations with the interests of the state has been proposed in the article.